Urgent engagement in 9/11 pregnant widows and their infants: Transmission of trauma. (31st January 2020) - Beebe, Beatrice; Hoven, Christina W.; Kaitz, Marsha; Steele, Miriam; Musa, George; Margolis, Amy; Ewing, Julie; Sossin, K. Mark; Lee, Sang Han
Abstract: The potential effects of maternal trauma on mother–infant interaction remain insufficiently studied empirically. This study examined the effects of the September 11, 2001, trauma on mother–infant interaction in mothers who were pregnant and widowed on 9/11, and their infants aged 4–6 months. Split‐screen videotaped interaction was coded on a one‐second basis for infant gaze, facial affect, and vocal affect; and mother gaze, facial affect, and touch. We examined the temporal dynamics of communication: self‐contingency and interactive contingency of behavior by time‐series methods. We documented heightened maternal and infant efforts at engagement in the 9/11 (vs. control) dyads. Both partners had difficulty tolerating moments of looking away as well as moments of negative behavior patterns. Heightened efforts to maintain a positive visual engagement may be adaptive and a potential source of resilience, but these patterns may also carry risk: working too hard to make it work. A vigilant, hyper‐contingent, high‐arousal engagement was the central mode of the interpersonal transmission of the trauma to these infants, with implications for intervention.